Effect of quitting smoking on health outcomes during treatment for tuberculosis: secondary analysis of the TB & Tobacco Trial - Siddiqi, Kamran; Keding, Ada; Marshall, Anna-Marie; Dogar, Omara; Li, Jinshuo; Huque, Rumana; Fatima, Razia; Khan, Amina; Elsey, Helen; Gabe, Rhian; Kotz, Daniel; Sheikh, Aziz (Thorax, 2022)
BackgroundDespite treatment, patients with tuberculosis (TB) who smoke have poorer outcomes compared with non-smokers. It is unknown, however, if quitting smoking during the 6 months of TB treatment improves TB outcomes.MethodsThe TB & Tobacco Trial was a double-blind, placebo-controlled randomised trial of cytisine for smoking cessation in 2472 patients with pulmonary TB in Bangladesh and Pakistan. In a secondary analysis, we investigated the hypothesis that smoking cessation improves health outcomes in patients during the TB treatment course. The outcomes included an eight-point TB clinical score, sputum conversion rates, chest X-ray grades, quality of life (EQ-5D-5L), TB cure plus treatment completion rates and relapse rates. These were compared between those who stopped smoking and those who did not, using regression analysis.ResultsWe analysed the data of 2273 (92%) trial participants. Overall, 25% (577/2273) of participants stopped smoking. Compared with non-quitters, those who quit had better TB cure plus treatment completion rates (91% vs 80%, p<0.001) and lower TB relapse rates (6% vs 14%, p<0.001). Among quitters, a higher sputum conversion rate at week 9 (91% vs 87%, p=0.036), lower mean TB clinical scores (−0.20 points, 95% CI −0.31 to −0.08, p=0.001) and slightly better quality of life (mean EQ-5D-5L 0.86 vs 0.85, p=0.015) at 6 months were also observed. These differences, except quality of life, remained statistically significant after adjusting for baseline values, trial arm and TB treatment adherence rates.ConclusionPatients with TB who stop smoking may have better outcomes than those who don’t. Health professionals should support patients in stopping smoking.